Multiband spectral‐spatial RF excitation for hyperpolarized [2‐13C]dihydroxyacetone 13C‐MR metabolism studies. Issue 4 (28th March 2016) - Marco‐Rius, Irene; Cao, Peng; von Morze, Cornelius; Merritt, Matthew; Moreno, Karlos X.; Chang, Gene‐Yuan; Ohliger, Michael A.; Pearce, David; Kurhanewicz, John; Larson, Peder E. Z.; Vigneron, Daniel B.
Abstract : Purpose: To develop a specialized multislice, single‐acquisition approach to detect the metabolites of hyperpolarized (HP) [2‐ 13 C]dihydroxyacetone (DHAc) to probe gluconeogenesis in vivo, which have a broad 144 ppm spectral range (∼4.6 kHz at 3T). A novel multiband radio‐frequency (RF) excitation pulse was designed for independent flip angle control over five to six spectral‐spatial (SPSP) excitation bands, each corrected for chemical shift misregistration effects. Methods: Specialized multiband SPSP RF pulses were designed, tested, and applied to investigate HP [2‐ 13 C]DHAc metabolism in kidney and liver of fasted rats with dynamic 13 C‐MR spectroscopy and an optimal flip angle scheme. For comparison, experiments were also performed with narrow‐band slice‐selective RF pulses and a sequential change of the frequency offset to cover the five frequency bands of interest. Results: The SPSP pulses provided a controllable spectral profile free of baseline distortion with improved signal to noise of the metabolite peaks, allowing for quantification of the metabolic products. We observed organ‐specific differences in DHAc metabolism. There was two to five times more [2‐ 13 C]phosphoenolpyruvate and about 19 times more [2‐ 13 C]glycerol 3‐phosphate in the liver than in the kidney. Conclusion: A multiband SPSP RF pulse covering a spectral range over 144 ppm enabled in vivo characterization of HP [2‐ 13 C]DHAc metabolism in rat liver and kidney. Magn Reson Med 77:1419–1428, 2017. © 2016 International Society for Magnetic Resonance in Medicine